Pengaruh Lingkungan Pergaulan Terhadap Keinginan Berbisnis Mahasiswa Ekonomi Syariah UIN K.H Abdurrahman Wahid Pekalongan - KHOTIBUL UMAM; Dyah Purbaningrum; Andhika Fahdkhansyah (Ebisma (Economics, Business, Management, & Accounting Journal), 2024)
This research aims to explore the influence of the social environment on the entrepreneurial intentions among Islamic Economics students. The social environment encompasses aspects such as family support, peer influence, academic community, mentors, and access to business information and opportunities. This study employs a descriptive qualitative method with data collection techniques through surveys and literature reviews. The results show that family support significantly impacts students' motivation, both in the form of moral support and financial assistance. The campus environment also plays a crucial role, where relationships with like-minded peers and business seminars can encourage entrepreneurial interest. Peer influence is found to be more dominant than faculty influence in shaping entrepreneurial interest due to the ease of sharing practical experiences. Additionally, media and information provide further motivation, although personal motivation remains the primary factor. Overall, this research emphasizes the importance of social support and environment in fostering entrepreneurial intentions among Islamic Economics students but also highlights that individual motivation is the key factor in the decision to start a business.